Rational Choice of Farmers in The Peat Land Conversion the Gambut sub-district, South Kalimantan - Budi Suryadi; Bachruddin Ali Ahmad; Husein Abdurahman; Syahrida Syahrida (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2019)
Peat land existence from day to day has decreased. Peat land deficit correlates with increasing development activity. From beginning until now peat lands are always faced with the need for development. The fact of Peat land is one of the land that used for the interest of development activities from government and private. This research used qualitative methods with a variety of phenomenology. Data collection techniques used a thick description and data analysis a used interactive model with four grooves that is data collection, data reduction, data presentation and conclusion continuously until saturated. Research result shows that farmers become an actor in the conversion process peat lands to other functions. Farmers action to sell peat lands to government and the private sector is rational choice at the time. Although selling land, farmers do not lose land because farmers have land abroad through purchase new land from money sales result peat lands previous.